(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
The Supervision of the economic administration of the Roman Curia ABSTRACT: This paper analyses the new system of supervision of the economic administration of the Roman Curia introduced by the Apostolic Constitution Praedicate Evangelium. Then, it focuses on the role that has been recently assigned in this area to the ‘Istituto per le Opere di Religione’ (IOR) and on that of the Vatican penal jurisdiction, both of which constitute highly innovative elements. SOMMARIO: 1. Le fonti normative della riforma - 2. Gli organismi di vigilanza - 3. Le plurime tipologie di vigilanza - 4. Analisi del nuovo sistema di vigilanza sull’amministrazione economica della Curia Romana - 5. Il ruolo peculiare dell’Istituto per le Opere di Religione - 6. La duplicazione del sistema di vigilanza tra Curia Romana e IOR - 7. Aspetti positivi del sistema e sue criticità - 8. Vigilanza canonica e supplenza della giurisdizione penale vaticana - 9. Osservazioni conclusive.